2019
DOI: 10.1002/adtp.201900169
|View full text |Cite
|
Sign up to set email alerts
|

A Versatile Polymer‐Based Platform for Intracellular Delivery of Macromolecules

Abstract: The plasma membrane barrier greatly restricts intracellular delivery of macromolecules. Currently available methods suffer from various limitations, including low delivery efficiency, high cytotoxicity, or incompatibility with a wider range of macromolecules or cell types. To overcome these issues, stimuli‐responsive polymers such as the bio‐inspired, pH‐responsive poly(l‐lysine isophthalamide) grafted with l‐phenylalanine at a stoichiometric ratio of 50% (PP50) can be used. In mildly acidic environments, the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 52 publications
0
9
0
Order By: Relevance
“…21 It has been reported that PP50 and hydrophilic dextran (polysaccharide of glucose) were present in a mixture with no obvious formation of complexes, suggesting limited interaction between the two components. 47 Similarly, PP50 would have limited interaction with hydrophilic trehalose (disaccharide of glucose), but it was argued that surrounding of PP50 by high concentrations of trehalose could inhibit its conformational change to hydrophobic compact polymer structures at mildly acidic pH, leading to inhibition of its membrane interaction and consequent reduction of trehalose loading and haemolysis. 21 Other researchers have reported similar observations on inhibition of peptide folding by high concentrations of trehalose, which can thickly cluster around constituent amino acids and shield them from each other.…”
Section: Impact Of Extracellular Trehalose Concentrationmentioning
confidence: 99%
“…21 It has been reported that PP50 and hydrophilic dextran (polysaccharide of glucose) were present in a mixture with no obvious formation of complexes, suggesting limited interaction between the two components. 47 Similarly, PP50 would have limited interaction with hydrophilic trehalose (disaccharide of glucose), but it was argued that surrounding of PP50 by high concentrations of trehalose could inhibit its conformational change to hydrophobic compact polymer structures at mildly acidic pH, leading to inhibition of its membrane interaction and consequent reduction of trehalose loading and haemolysis. 21 Other researchers have reported similar observations on inhibition of peptide folding by high concentrations of trehalose, which can thickly cluster around constituent amino acids and shield them from each other.…”
Section: Impact Of Extracellular Trehalose Concentrationmentioning
confidence: 99%
“…Polymer is a kind of macromolecular compound synthesized through the addition or condensation polymerization of monomers with various reactive groups, which is now being widely applied in the exploitation and development of drug delivery systems owing to its good biocompatibility, ease of chemical modification, controllable molecular weight and structure, etc . In the past decades, synthetic polymers such as poly­(lactic- co -glycolic acid) (PLGA) and polyethylene glycol (PEG) have been developed and approved by the FDA as long-acting formulations for delivery of protein/peptide therapeutics such as Adagen, Eligard, Bydureon, etc ., which are now vastly applied in the clinical treatment of various diseases such as severe combined immunodeficiency (SCID), cancer, and diabetes. Natural polymers such as various kinds of polysaccharide are now being investigated extensively as carriers for loading biomacromolecules such as proteins attributed to their abundant sources, low price, and good biocompatibility and biodegradability, holding great potential in the future for resolving the issues previously mentioned. …”
Section: Polymer-based Systemsmentioning
confidence: 99%
“…Mechanistic insights suggest that phenylalanine modified PLP induced red blood cell membrane thinning of 35–40% normal thickness at endosomal pH, thus facilitating the transport of membrane-impermeable small molecular cargos (Lynch et al, 2011 ). Further real-time imaging showed that even large molecules such as FITC-labeled dextran of different molecular weights (10–500 kDa) and green fluorescence protein could be delivered to different mammalian cells after co-incubation with phenylalanine modified PLP at pH 6.5 (Kopytynski et al, 2020 ). Such a convenient and flexible method provides a versatile platform for cell engineering ex vivo .…”
Section: Amphiphilic Carboxylate Polymers: History and Recent Developmentmentioning
confidence: 99%
“…(Wang, 2018;Evans et al, 2019). Albeit less renowned, recent studies show their emerging potentials for proteins, genes, and vaccine delivery (Mukalel et al, 2018;Qiu et al, 2018;Evans et al, 2019;Jacobson et al, 2019;Kopytynski et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation